Application of Apriori Algorithm in Determining Behavioral Patterns and Lifestyle of GERD Patients - pramudhita, chika; Buaton, Relita; Sitompul, Melda Pita Uli (International Journal of Informatics, Economics, Management and Science, 2024)
Gastroesophageal Reflux Disease (GERD) is a condition of reflux of stomach contents into the esophagus which can cause typical symptoms such as heartburn (burning in the epigastric region), acid regurgitation (bitter taste in the mouth), nausea, and dysphagia which can result in damage to the esophageal mucosa and in the long term can cause complications such as Barrett's esophagus. Based on data on patients with GERD disease in 2020-2023, there were 521 patients obtained at Bidadari Binjai General Hospital, with differences in prevalence caused by socioeconomic and lifestyle changes that can increase the incidence of GERD. The purpose of this study is to obtain the results of the combination between item-sets on the behavior patterns and lifestyles of GERD sufferers which are expected to help the agency in processing data on GERD sufferers into more effective information to determine the behavior patterns and lifestyles of GERD sufferers with the Apriori Algorithm method. From the research conducted, the results obtained rules that meet the value of 30% support and 100% confidence, if unhealthy eating patterns are often late eating, then unhealthy lifestyles are often done sleeping after eating and smoking.